A major practicum report for Virginia Food , Incorporated in Cogon-Canamucan, Compostela, Cebu - Abonado, Rowena Fuentes (2008)
As part of the curriculum of the Bachelor of Science in Food Technology of the University of the Philippines Mindanao, 288 hours of plant practice was conducted at Virginia Food, Incorporated (VFI) from April to May 2007. The plant practice aimed to provide the intern with exposure and training as a quality assurance checker on the different activities in the meat processing line. Through plant practice, the intern was able to apply all the relevant insights she learned from the academe. She was also able to gather necessary information about the plant including the company profile and organizational structure, its mission and vision, production and processing systems and the protocols implemented to achieve high product quality and to ensure food safety. The intern was also harnessed in decision-making. This manuscript is made to document the intern?s experience during the plant practice and to present a comprehensive technical analysis on the different process operations in a meat processing plant